Relative larvicidal property of common oxide nanostructures against Culex quinquefasciatus. Issue 5 (3rd June 2020) - Chakrabarti, Adrita; Patra, Prasun
Abstract : Common oxide nanostructures such as silicon‐di‐oxide, magnesium‐oxide, zinc‐oxide, and copper‐oxide (CuO) having useful functional and bioactive properties have been synthesised and characterised. All these nanostructures have been found to be larvicidal towards Culex quinquefasciatus mosquito especially against lower instars in comparison with higher instars in 48 h. Only, CuO is larvicidal against late instar stages after 48 h. Moreover, CuO is larvicidal against first instar stages after 24 h (LC50 157 mg/l). However, none of these nanostructures are pupicidal. Post mortality larval morphology was found to be distorted under bright field microscopy and scanning electron microscopy images of affected larval surface appeared to be rough and uneven. Fluorescent images showed that nanostructures infiltrated inside visceral organs of larvae. Nanostructures also caused tissue oxidative stress in larvae. These results indicate that above stated oxide nanostructures are effective larvicidal agents against early instar stages of Culex larvae.